Biopolymers Lignin, Proteins, Bioactive Nanocomposites - Abe, Akihiro; Dusˇek, Karel; Kobayashi, Shiro (Advances in Polymer Science, 2010)
Table of Contents Lignin Structure, Properties, and Applications Hyoe Hatakeyama and Tatsuko Hatakeyama Tensile Mechanics of α-Helical Coil Springs Atsushi Ikai Bioactive Polymer/Hydroxyapatite (Nano)composites for Bone Tissue Regeneration Kinga Pielichowska and Stanislaw Blazewicz.